Treatment of psoriasis with etanercept in immunocompromised patients: Two case reports - De Simone, Clara; Perino, Francesca; Caldarola, Giacomo; D’Agostino, Magda; Peris, Ketty (Journal of international medical research, 2016)
Tumour necrosis factor (TNF)-α blocking agents have revolutionized the treatment of psoriasis and psoriatic arthritis. Concerns remain about increased susceptibility to infection and onset of malignancies, and the use of TNF-α agents in patients with HIV infection or undergoing immunosuppressant treatment is debated. We report cases of severe plaque psoriasis in a patient with HIV infection and in a liver transplant recipient who were successfully treated with etanercept, an anti-TNF-α agent, without notable side-effects.